Knowledge and practice of hand hygiene among the doctors of Patan Hospital, Nepal - Bhatt, Prashant Raj; Paudel, Ujjawal; Koirala, Tapendra; Shrestha, Purnima; Mishra, Ujjwal Kumar (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Hand hygiene is the most effective infection prevention measure. This research aims to find out the knowledge and practice of hand hygiene among the doctors of major departments of Patan Hospital. Method: A cross-sectional study was conducted among doctors of selected departments of Patan Hospital, Lalitpur, Nepal. The knowledge of hand hygiene was assessed using a WHO knowledge questionnaire. The practice was assessed using a WHO observation checklist. The data was recorded in Epi-info and the analysis was done for knowledge score and compliance with practice using SPSS v15. A p-value of <0.05 was considered statistically significant. Result: A total of 104 (98%) of the participants completed each part (knowledge and practice) of the study. The overall mean score (± SD) was 64% ± 8 on knowledge questions about hand hygiene. Knowledge of hand hygiene was not significantly different among departments (p=0.351) and gender (p=0.994). Out of 1022 opportunities, the compliance of hand hygiene among the doctors was 532(52%). The highest compliance for hand hygiene was after exposure to body fluids 93%. The mean time taken for hand rub was 8 seconds and the mean steps performed were 4 out of 8. Compliance with hand hygiene was statistically significant among departments (p= 0.001). However, it was not statistically significant among gender(p=0.198). Conclusion: Participants performed relatively well with a moderate score (64%) on knowledge questions but it was not reflected in practice (overall compliance 52%). The majority performed hand hygiene after body fluid exposure (93%) and after touching patients (64%).